An Empirical Study of Financial Shared Services: Understanding of an organization moves towards establishing financial shared service as a strategic finance function - Nik Mustaffa, Nik Azah Karimah (2009)
This paper is prepared to understand an organization moves towards establishing financial shared service as a strategic finance function. The research is conducted by selected few multinational organizations from oil and gas industry to analyze the purpose of the move, how organizations are restructure and values generated from the financial shared services. The research also will extend towards identifying various challenges faced by the organizations during the restructuring process. The issues encountered after the implementation also will be addressed.